Musicians as workers and music as labor: the formation of a research field in the area of music in Brazil (Orfeu, 2024)
Through this article, we analyze the formation of a new research field in the area of Music in Brazil, dedicated to the study of the work of musicians. To this end, we conducted a bibliographic and documentary investigation that uses as a criterion for identifying this field the thematic territory defined by musicians as workers and/or music as work, in different approaches and conceptions. We provide an overview of how the professional life of musicians has been addressed in academic production and through various university initiatives, outlining the porous boundaries that signal the emergence of this new research field in music in Brazil. In contrast to the lack of declared interest of postgraduate programs in Music in understanding the work realities of musicians, there has been a significant increase in research on the subject and related topics, as evidenced by the number of academic productions that dialogue with them, the expansion of the space for debates in scientific events in the area and the presence of teaching, extension and university research actions linked to the subject. Based on the survey and the analyses carried out, we believe that there is a new field of research in formation, focused on the study of the work field of Music.
Keywords: work; musicians; music research in Brazil; musicians as workers; music as labor